PENGARUH PEMBERDAYAAN DAN MOTIVASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR GURU SD NEGERI DI KECAMATAN BEKASI SELATAN - Erna Risnawati (Jurnal Manajemen Pendidikan, 2015)
The purpose of this research is to determine the effect of empowerment and motivation on organizational citizenship behavior in this teacher primary school south bekasi. The research methodology was survey which were selected by simple random sampling technique. Analysis and interpretation of the data indicate that (1) empowerment has a positive direct effect in organizational citizenship behavior, (2) motivation has a positive direct effect in organizational citizenship behavior, (3) empowerment has a positive direct effect in motivation.